2002
DOI: 10.1046/j.1365-2133.2002.05095.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe panniculitis caused by homozygous ZZ alpha1-antitrypsin deficiency treated successfully with human purified enzyme (ProlastinR)

Abstract: Severe panniculitis caused by alpha1-antitrypsin deficiency is very rare even though the ZZ phenotype occurs in 1 : 3500 of the population of northern Europe. We describe a 33-year-old woman with rapidly progressing panniculitis and extensive skin necrosis with multiple life-threatening complications. Initial treatment followed by maintenance therapy with human purified enzyme (Prolastin, Bayer, Bridgend, U.K.) has been life-saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 5 publications
(6 reference statements)
0
20
0
1
Order By: Relevance
“…Several case studies have revealed that infusion of a higher dose of AAT augmentation therapy compared to that required for the treatment of lung disease, successfully managed and reduced inflammation associated with severe panniculitis in AATD individuals with the ZZ phenotype (Al-Niaimi and Lyon 2011; Blanco et al 2011;Chowdhury et al 2002;Dowd et al 1995;Gross et al 2009). The prevalence of panniculitis as a complication of AATD is infrequent, with an occurrence of approximately 0.1%.…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Panniculmentioning
confidence: 99%
“…Several case studies have revealed that infusion of a higher dose of AAT augmentation therapy compared to that required for the treatment of lung disease, successfully managed and reduced inflammation associated with severe panniculitis in AATD individuals with the ZZ phenotype (Al-Niaimi and Lyon 2011; Blanco et al 2011;Chowdhury et al 2002;Dowd et al 1995;Gross et al 2009). The prevalence of panniculitis as a complication of AATD is infrequent, with an occurrence of approximately 0.1%.…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Panniculmentioning
confidence: 99%
“…Appropriate histology and serum concentration of AAT below 30% of the lower reference value prior to the treatment further support the diagnosis of AAT deficiency-related wound healing impairment. Successful augmentation therapy of AAT deficiency-associated panniculits has been described earlier (21). While other cases reported in the literature were treated with either tetracycline, steroids, non-steroidal anti-inflammatory drugs or hydroxychloroquine, individualised Prolastin ® therapy in terms of starting time of application and dosage showed to be the most effective treatment strategy (22).…”
Section: Resultsmentioning
confidence: 97%
“…Many clinicians regard dapsone as the initial treatment of choice, based on modest efficacy and reasonable expense. At the same time, though described in only 2 reports to date [19, 33], intravenous augmentation therapy has consistently been associated with prompt resolution of the signs and symptoms of AAT deficiency-associated panniculitis. Reports to date have described conventional doses of 60 mg/kg body weight once weekly, which conferred only incomplete benefit in our patient.…”
Section: Discussionmentioning
confidence: 99%